2021
DOI: 10.1002/adfm.202102599
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Bicolorimetric Polyacrylamide/Chitosan Hydrogels for Smart Real‐Time Monitoring and Promotion of Wound Healing

Abstract: Real‐time monitoring of wound healing remains a major challenge in clinical tissue regeneration, calling the need for the development of biomaterial‐guided on‐site monitoring wound healing technology. In this study, multifunctional double colorimetry‐integrated polyacrylamide‐quaternary ammonium chitosan‐carbon quantum dots (CQDs)‐phenol red hydrogels are presented, aiming to simultaneously detect the wound pH level, reduce bacterial infection, and promote wound healing. The hybridization of CQDs and pH indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(118 citation statements)
references
References 81 publications
0
106
0
Order By: Relevance
“…They took advantage of regenerative immunotherapy, and demonstrated that the hydrogel could upregulate M2 macrophage, which enabled anti-inflammation and stimulated angiogenesis, thereby significantly improving diabetic wound healing. Recently, Zheng et al reported a smart hydrogel fabricated from polyacrylamide-quaternary ammonium chitosan-carbon quantum dots-phenol red system to monitor and treat wound healing ( Zheng K. et al, 2021 ). The hydrogel had antibacterial activities, and its coupling with pH-responsive carbon quantum dots and phenol red indicator enabled it to detect the pH changes of the wound, thereby indirectly monitoring the real-time wound healing process through the change of color in a noninvasive way.…”
Section: The Philosophy Of Wound Healing Scaffoldsmentioning
confidence: 99%
“…They took advantage of regenerative immunotherapy, and demonstrated that the hydrogel could upregulate M2 macrophage, which enabled anti-inflammation and stimulated angiogenesis, thereby significantly improving diabetic wound healing. Recently, Zheng et al reported a smart hydrogel fabricated from polyacrylamide-quaternary ammonium chitosan-carbon quantum dots-phenol red system to monitor and treat wound healing ( Zheng K. et al, 2021 ). The hydrogel had antibacterial activities, and its coupling with pH-responsive carbon quantum dots and phenol red indicator enabled it to detect the pH changes of the wound, thereby indirectly monitoring the real-time wound healing process through the change of color in a noninvasive way.…”
Section: The Philosophy Of Wound Healing Scaffoldsmentioning
confidence: 99%
“…The results showed that these delivery systems exhibit targeted drug delivery to gastric sites for the treatment of H. pylori , along with a suitable drug-release pattern. 121 Chitosan exhibits excellent adhesion and antibacterial properties, 122 and chitosan microspheres impart a good loading capacity and controlled-release capability to delivery systems, along with specific adhesion to H. pylori . 123 , 124 Gonçalves et al reported that chitosan microspheres exhibit the highest adherence to H. pylori at pH 6, and the microspheres are significantly more effective against BabA/SabA + H. pylori (76% reduction) strain than the BabA + /SabA H. pylori strain (50% reduction).…”
Section: Nanoparticlesmentioning
confidence: 99%
“…The use of smartphones can not only achieve in vivo monitoring but also perform real-time remote evaluations. Zheng et al [ 154 ] presented multifunctional double colorimetry-integrated polyacrylamide–quaternary ammonium chitosan–carbon quantum dots (CQDs)–phenol red hydrogels to detect the wound pH level ( Figure 6 c). In the context of both ultraviolet and visible light, on-site wound pH signals could be accurately indicated through the RGB analysis of the images collected by smartphones; thus, dynamic wound status could be reflected for a real-time evaluation in a remote approach.…”
Section: Key Wound Marker Detectionmentioning
confidence: 99%
“…Copyright (2019) John Wiley and Sons. ( c ) A remote approach of dynamic wound status evaluation with the RGB analysis of the images collected by smartphones [ 154 ]. Copyright (2021) John Wiley and Sons.…”
Section: Figurementioning
confidence: 99%